2014
DOI: 10.1095/biolreprod.112.105809
|View full text |Cite
|
Sign up to set email alerts
|

Regulated Wnt/Beta-Catenin Signaling Sustains Adult Spermatogenesis in Mice1

Abstract: The importance of Wnt signaling for postnatal testis function has been previously studied in several mouse models, with chronic pathway disruption addressing its function in Sertoli cells and in postmeiotic germ cells. While chronic beta-catenin deletion in Sertoli cells does not profoundly affect testis development, new data indicate that Wnt signaling is required at multiple stages of spermatogenesis. We used two mouse models that allow acute disruption of Wnt signaling to explore the importance of regulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 45 publications
2
56
0
1
Order By: Relevance
“…For example, we detected the expression of Wnt3 in round spermatids and elongating spermatids, Wnt3a in round spermatids, Wnt5a in Leydig cells and peritubular myoid cells, Wnt7a in pachytene spermatocytes and round spermatids, and Wnt8b in round spermatids. These gene-expression patterns are compatible with previously published transcriptional profiling data (37)(38)(39).…”
Section: Sertoli Cells Secrete Wnt6 As a Paracrine Signal For Undiffesupporting
confidence: 89%
See 1 more Smart Citation
“…For example, we detected the expression of Wnt3 in round spermatids and elongating spermatids, Wnt3a in round spermatids, Wnt5a in Leydig cells and peritubular myoid cells, Wnt7a in pachytene spermatocytes and round spermatids, and Wnt8b in round spermatids. These gene-expression patterns are compatible with previously published transcriptional profiling data (37)(38)(39).…”
Section: Sertoli Cells Secrete Wnt6 As a Paracrine Signal For Undiffesupporting
confidence: 89%
“…In addition, spermatid-specific β-catenin CKO mediated by Prm1-Cre has been shown to cause impaired fertility as a result of reduced sperm counts (50). Another group reported disrupted spermatogenesis in both loss-and gain-of-Wnt signaling function experiments using AhCre (37). However, it is difficult to compare these phenotypes to those observed by us because of differences in target cell types or leaky Cre activity before induction.…”
Section: Discussionmentioning
confidence: 81%
“…However, during T-cell development, Sox13 also directly interacts with the lymphoid enhancer-binding factor (TCF/LEF) to cause repression of Wnt target gene expression [37]. Interestingly, the use of mouse models revealed that the Wnt signaling pathway is required for normal spermatogenesis [81] and that Wnt4 inhibits testosterone synthesis by repressing SF-1 (NR5A1)/beta-catenin synergy in Leydig cells [82]. Thus, Sox13 may regulate steroidogenic gene (A) (B) Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It seems likely that in rat testes b-catenin serves as an important member of the cell adhesion complex rather than a transcriptional regulator of the Wnt signaling pathway. On the other hand, Kerr et al (2014) have recently detected nuclear b-catenin in murine spermatocytes and spermatids and based on mouse model with b-catenin mutation (AhCre Ctnnb1 fl/fl ) proposed Wnt/b-catenin signaling as required at several stages of spermatogenesis. It should be added that other authors also reported that deletion of b-catenin gene or its stabilizing mutation in germ cells caused germ cell deficiency and spermatogenic failure (Kimura et al, 2006;Chang et al, 2011).…”
Section: (A) (B)mentioning
confidence: 99%
“…It has been shown that perturbation of b-catenin signaling in embryonic testis caused testicular degeneration, Mullerian duct regression and testis maldescent (Chang et al, 2008;Tanwar et al, 2010;Kobayashi et al, 2011). Recently, involvement of Wnt/b-catenin signaling in spermatogenesis has also been explored (Kerr et al, 2014).…”
Section: Introductionmentioning
confidence: 99%